Bias voltage dependence of superlubricity lifetime of hydrogenated amorphous carbon films in high vacuum. (January 2018) - Cui, Longchen; Zhou, Hui; Zhang, Kaifeng; Lu, Zhibin; Wang, Xianrong
Abstract: We deposit hydrogenated amorphous carbon (a-C:H) films by magnetron sputtering of graphite in an Ar + C2 H2 mixture at various bias voltages. The mechanical properties, Raman spectra, and high-vacuum frictional behaviors of the a-C:H films indicate that the films deposited at bias 0, –50, and −100 V are polymer-like carbon (PLC) films and the film deposited at −150 V is a diamond-like carbon (DLC) film. The lifetimes of superlubricity, with friction coefficient ∼0.002, of the PLC films in high-vacuum increase from 10000 to 28000 cycles with increasing bias, although the film thicknesses decrease. The DLC film's wear-life is ∼600 cycles. The enhanced wear-resistance in PLC films is attributed to improvement of the crosslinking degree of the PLC network and the film compactness. Graphical abstract: Highlights: Polymer-like carbon (PLC) films are deposited by reactive magnetron sputtering. Superlubricity lifetime of PLC films in high vacuum increases with bias voltage. The prolonged lifetime is due to enhanced crosslinking level and film compactness.